Towards net-zero in steel production: Process simulation and environmental impacts of carbon capture, storage and utilisation of blast furnace gas - Harish K. Jeswani; Santiago Zapata-Boada; Vincenzo Spallina; Adisa Azapagic (Carbon Capture Science & Technology)
Blast furnace gas (BFG), the main off-gas product of primary steel production, significantly contributes to the overall CO2 emissions from primary steel production. Various decarbonisation strategies are currently being explored to mitigate these emissions. This paper combines process simulation with life cycle assessment to estimate the environmental impacts of different BFG decarbonisation scenarios involving carbon capture and utilisation (CCU) and carbon capture and storage (CCS). For CCU scenarios, a novel approach is considered that valorises BFG into transport fuels, utilising chemical looping with reverse water-gas shift reaction (CL-RWGS) followed by the Fischer-Tropsch process. For CCS, two pre-combustion capture processes are evaluated. The results indicate that the CCU-based scenarios can reduce the climate change impact of steel production by 11–45 %, while the CCS scenarios can achieve reductions of 17–34 %. However, these reductions come with significant increases in other environmental impacts. In the CCU-based scenarios, freshwater consumption, land use, human toxicity, terrestrial ecotoxicity, ionising radiation, and ozone depletion impacts increase by 60 % to as much as 60 times, primarily due to the large quantities of hydrogen required for the CL-RWGS process. Similarly, the energy penalties associated with the CCS process also increase other impacts, though the increases are less pronounced than in the CCU scenarios. Given that the CL-RWGS-based CCU technologies are still in early development stages, further research should focus on improving both the CCU process and hydrogen production methods.